2010
DOI: 10.1128/jcm.01642-09
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Immuno Card Toxins A&B and the New Semiautomated Vidas Clostridium difficile Toxin A&B Tests for Diagnosis of C. difficile Infection

Abstract: ᰔWe recently showed the ImmunoCard Toxins A&B test (ImmunoCard) (Meridian) to be as specific as and more sensitive than two widely used immunochromatographic tests to diagnose Clostridium difficile infection (CDI) (1). The Vidas C. difficile Toxin A&B test (Vidas-AB) (bioMérieux) is a new enzyme-linked fluorescent immunoassay (ELFA) that detects toxins A and B. As it is automated, it reduces the workload compared to traditional enzyme-linked immunosorbent assays. Our objectives were to evaluate the performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Selection bias is always a possibility in case-control studies, because the selection of controls is often challenging. We used a diagnostic tool with high specificity (98%) and only moderate sensitivity (69.4%) for CDI [ 14 ]; consequently, it is probable that our sample failed to include less severe cases of CDI. Nevertheless, our strategy of selecting appropriate controls with non- C. difficile -related hospital-acquired diarrhea and matching them to our study subjects was designed to minimize the possibility of selection bias by ensuring that the distributions of possible confounders did not differ substantially between cases and controls [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selection bias is always a possibility in case-control studies, because the selection of controls is often challenging. We used a diagnostic tool with high specificity (98%) and only moderate sensitivity (69.4%) for CDI [ 14 ]; consequently, it is probable that our sample failed to include less severe cases of CDI. Nevertheless, our strategy of selecting appropriate controls with non- C. difficile -related hospital-acquired diarrhea and matching them to our study subjects was designed to minimize the possibility of selection bias by ensuring that the distributions of possible confounders did not differ substantially between cases and controls [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, all samples of stool in the hospital's microbiology laboratory electronic database between January 2010 and July 2012 were identified. These samples were analyzed for the presence of toxins A and B of C. difficile using an enzyme-linked fluorescent immunoassay (Vidas A & B, BioMérieux, Durham, NC, USA) [ 14 ] according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…At first, laboratories used EIAs that detected only toxin A but, with the dissemination and higher frequency of strains toxin A-/toxin B+ producing CDI, these were replaced by EIAs capable of detecting both toxins [80][81][82][83]. Some comparative studies have shown that EIAs have sensitivity values of 40-60% when compared with toxigenic cultures [84][85][86][87][88][89][90]. On the other hand, the specificity of most of these tests is higher than 90%.…”
Section: Question 6 What Combination Of Laboratory Tests Is Most Cosmentioning
confidence: 99%
“…Immunoassays are directed to either an enzyme carried by C. difficile (glutamate dehydrogenase) or toxins produced by C. difficile (TcdA and TcdB). These immunoassays are more rapid diagnostic tests, but it is well known that direct immunoassay testing of stool samples lacks adequate sensitivity for the detection of toxigenic C. difficile , with a sensitivity of 60–70 % [ 1 3 ]. Real-time polymerase chain reaction (PCR)-based diagnosis has proved to be highly sensitive and has become more widely available [ 1 , 4 ].…”
Section: Introductionmentioning
confidence: 99%